Cardiovascular disease and risk factors in adults with diabetes mellitus in Hungary: a population-based study - Ulambayar, Battamir; Ghanem, Amr Sayed; Kovács, Nóra; Trefán, László; Móré, Marianna; Nagy, Attila Csaba (Frontiers in Endocrinology, 2023)
Diabetes mellitus (DM) and cardiovascular disease (CVD) such as acute myocardial infarction, stroke, and coronary artery disease are highly prevalent conditions that are responsible for significant morbidity and mortality, particularly in Hungary. The conditions are attributed to identical risk factors, and individuals with DM are primarily susceptible to cardiovascular complications, which are the leading causes of death and disability in patients with DM. The objective of this study was to estimate the prevalence of CVD in individuals with DM and to investigate the association between potential risk factors and the presence of CVD among individuals with DM in a population-based sample. The study was based on data from three waves of the European Health Interview Surveys (EHIS) conducted in Hungary in 2009, 2014, and 2019. Our findings suggest that the prevalence of CVD among patients with DM decreased during the study period and that socioeconomic factors, cardiometabolic risk factors including high blood pressure and high cholesterol, and depression are major contributors to CVD burden in patients with DM in Hungary. Our findings suggest the importance of regular check-up for hypertension and hypercholesterolemia, better focus on socioeconomic status, as well as ongoing monitoring of mental health among patients with diabetes. Further research is needed to understand the potential causes behind the observed decrease in CVD prevalence.